"The Intelligence of Nations": Smart but not Wise—A Comment on Hunt (2012). (March 2013) - Sternberg, Robert J.
I argue in this comment that Hunt's analysis of the intelligence of nations is smarter than it is wise. It is based on too narrow a conception of intelligence. It also conflates correlation and causation with regard to the relation between IQ and socially defined success, both individual and familial. I suggest that a better approach might be to compare nations as well for their creativity and wisdom.